Penerapan Pembelajaran Berdiferensiasi dan Inklusif di Kelas XI SMA Kemala Bhayangkari 1 Kubu Raya - Buri, Viktorina; Putra, Ikhza Mahendra; Priyadi, Antonius Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to identify the implementation of differentiated instruction in high school classrooms. The research focuses on adaptive teaching strategies tailored to the needs of students, including those with sensory disabilities such as visual and hearing impairments. A qualitative method with a case study approach was used to explore the in-depth application of differentiated instruction in real-world contexts. Data collection was conducted through direct observation, in depth interviews with teachers and students, and document analysis, such as academic records and lesson plans. The study focuses on eight students as a sample within a class of 30 students in the XI B grade at Kemala Bhayangkari 1 High School, Kubu Raya. Analysis was carried out using a qualitative case study approach to understand how teachers adapt and implement differentiated teaching strategies in an inclusive classroom. The application of differentiated instruction strategies at Kemala Bhayangkari 1 High School, particularly in grade XI B, successfully created an inclusive learning environment for students with mild sensory disabilities. The results show that these strategies enhanced active participation and motivation among students with sensory impairments. However, challenges such as limited resources and a lack of teacher training hindered optimal implementation. Differentiated instruction has great potential to create an inclusive and effective learning environment in inclusive classrooms. However, improving access to tailored resources, fostering closer collaboration between teachers, support staff, and parents, as well as providing professional development for teachers, is necessary to accommodate the diverse needs of students more effectively. Thus, differentiated instruction holds significant promise in fostering inclusive and effective learning environments in inclusive settings.